Antibody-removal therapies for de novo DSA in pediatric intestinal recipients: Why, when, and how? A single-center experience - Lasa-Lázaro, María; Ramos-Boluda, Esther; Mancebo, Esther; Castro-Panete, María José; González-Sacristán, Rocío; Serradilla, Javier; Andrés-Moreno, Ane Miren; Hernández-Oliveros, Francisco; Paz-Artal, Estela; Talayero, Paloma (Frontiers in Pediatrics, 2023)
BACKGROUND Donor specific anti-HLA antibodies (DSA) impact negatively on the outcome of intestinal grafts. Although the use of antibody-removal therapies (ART) is becoming more frequent in the last years, issues regarding their timing and effectiveness remain under discussion. METHODS In the present study we report our experience with 8 ART procedures (based on plasmapheresis, intravenous immunoglobulin and rituximab) in 8 pediatric intestinal and multivisceral transplants with de novo DSA (dnDSA). RESULTS ART was performed when dnDSA appeared in two contexts: A) concomitant with rejection (acute or chronic) or B) without rejection or any other clinical symptom. Complete DSA removal was observed in 7/8 cases showing an effectiveness of 88%. In the group treated for dnDSA without clinical symptoms, the success rate was 100%, with complete DSA removal and without rejection afterwards. Shorter time between DSA detection and ART performance appeared as a significant factor for the therapy success (p=0.0002). DSA against HLA-A and DQ alleles were the most resistant to ART, whereas anti-DR DSA were the most sensitive. Additionally, the 8-year allograft survival in recipients undergoing ART was similar to those without DSA, being significantly lower in non-treated DSA positive recipients (p=0.013). CONCLUSION The results confirm the ART effectiveness in terms of DSA removal and allograft survival and encourage their early use even in the absence of clinical symptoms.